Optical tractography of the mouse heart using polarization-sensitive optical coherence tomography - Wang, Yuanbo; Yao, Gang (Biomedical optics express, 2013)
We developed a method to image myocardial fiber architecture in the mouse heart using a Jones matrix-based polarization-sensitive optical coherence tomography (PSOCT) system. The "cross-helical" laminar structure of myocardial fibers can be clearly visualized using this technology. The obtained myocardial fiber organization agrees well with existing knowledge acquired using conventional histology and diffusion tensor magnetic resonance imaging.